Antimicrobial Resistance Situation in Indonesia: A Challenge of Multisector and Global Coordination. (7th February 2022) - Siahaan, Selma; Herman, Max J.; Fitri, Nyoman
Abstract : High levels of antimicrobial resistance (AMR) in Indonesia are caused by the use of inappropriate antimicrobials (AM) in healthcare services and the livestock and fisheries sector. The available data and information about overused antibiotics and the AMR threat in Indonesia are limited. The aim of the study is to describe the AMR situation in Indonesia based on perceptions of government officials, health professionals, and the community to determine actions needed to develop AMR-related strategy and policy. The study was done in eight provinces in Indonesia and included reviewing AMR-related policy, collecting antibiotic use reports in primary health care from health offices and hospitals, and conducting in-depth interviews and focus group discussions with informants from health and nonhealth sectors. The results of the study show that AM misuse happens not only in healthcare facilities but also in communities. Medical officers are unfamiliar with AMR-related policy, as are officers in the livestock and fisheries sectors. There is limited coordination between sectors regarding the AMR situation in Indonesia. The government has to take stronger measures to oversee better implementation of AMR policies.